Re “Inhaled Corticosteroid Particle Size and Risk of Hospitalization Rue to Exacerbations and All-Cause Mortality in Patients With Chronic Obstructive Respiratory Disease. A Nationwide Cohort Study”. Heerfordt et al [Letter] - Hubbard R; Carter V; Henley W; Price D (International Journal of COPD)
Richard Hubbard, Victoria Carter, William Henley, David Price Observational and Pragmatic Research Institute, Cambridge, UKCorrespondence: David Price, Observational and Pragmatic Research Institute, 5 Coles Lane, Cambridge, CB24 3BA, UK, Email dprice@opri.sg